2005
DOI: 10.1517/14740338.4.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of sodium valproate

Abstract: The teratogenicity of the widely popular antiepileptic drug (AED) and mood stabiliser sodium valproate (also known as valproate, VPA) has been evidenced by previous research; however, these findings have often been limited by a small population sample of exposed women and a retrospective study design. Many factors contribute to the teratogenicity of VPA. These include the number of drugs that are co-administered, drug dosage, differences in maternal and/or infant metabolism, the gestational age of the fetus at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 69 publications
3
100
0
4
Order By: Relevance
“…Direct inhibition of HDAC by VPA (Göttlicher et al, 2001;Gurvich et al, 2004) is thought to give rise to teratogenicity (Koren et al, 2006;Jentink et al, 2010), causing a variety of major and minor malformations, including neural tube defects, Seizure Control by Medium Chain Fatty Acid Derivatives cleft lip and palate, cardiovascular abnormalities, genitourinary defects, developmental delay, endocrinological disorders, limb defects, and autism (Alsdorf and Wyszynski, 2005). This biochemical activity provides a crucial side-effect profile to consider in the development of carboxylic acid-based antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Direct inhibition of HDAC by VPA (Göttlicher et al, 2001;Gurvich et al, 2004) is thought to give rise to teratogenicity (Koren et al, 2006;Jentink et al, 2010), causing a variety of major and minor malformations, including neural tube defects, Seizure Control by Medium Chain Fatty Acid Derivatives cleft lip and palate, cardiovascular abnormalities, genitourinary defects, developmental delay, endocrinological disorders, limb defects, and autism (Alsdorf and Wyszynski, 2005). This biochemical activity provides a crucial side-effect profile to consider in the development of carboxylic acid-based antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The data from this and other class I Hdac knockout studies indicate that HDAC inhibitors might be teratogenic, and indeed, this has been demonstrated in rodent models (Menegola et al 2006). Craniofacial abnormalities have also been described in children born from mothers treated with the HDAC inhibitor valproic acid (Alsdorf and Wyszynski 2005).…”
Section: Implication For Human Diseasementioning
confidence: 55%
“…Although lithium and valproic acid have a teratogenic effect, in some studies it was seen that these substances did not increase the incidence of major malformations. The negative information previously existing about these drugs was not confirmed by later research (12,13).…”
mentioning
confidence: 77%